Distribution of landslides reconstructed from inventory data and estimation of landslide susceptibility in Hungary - Józsa, Edina; Lóczy, Dénes; Soldati, Mauro; Drăguţ, Lucian Daniel; Szabó, József (Hungarian Geographical Bulletin, 2019)
The complexity of landslides makes it difficult to predict the spatial distribution of landslide susceptibility and hazard. Although in most European countries the basic preconditions for the occurrence of mass movements (rocks and topography) have been mapped in detail, the triggering factors (e.g. precipitation or earthquakes) are much less predictable. A detailed nation-wide inventory for Hungary provides a unique base for landslide susceptibility mapping. As the methodology for the assessment the technique applied in the ELSUS 1000 project was selected. The micro-regions of Hungary were identified where mass movements contribute to land degradation. The paper provides a statistical evaluation of the distribution of landslides, depicts landslide susceptibility on maps and reveals the role of anthropogenic factors in the generation of mass movements. The mid-resolution elevation model (SRTM1), land cover data (CLC50) and surface geology database (Mining and Geological Survey of Hungary) allowed for the derivation of a landslide susceptibility map more detailed than before. Along with its background information the map reflects and explains the differences in landslide susceptibility among the individual hilly and mountainous regions.